Perspectives on assessing physical fitness and functionality in older adults (ACTIVIDAD FÍSICA Y DESARROLLO HUMANO, 2012)
The following article reflects on the fundamentals, experiences, and current perspectives on the evaluation of parameters associated with the physical condition of functionally independent older adults, with the aim of advancing the identification of methods geared toward this end that are suited to the conditions and needs of our environment. Thus, the most widely used and best validated test batteries for assessing this population are described and contextualized, concluding with an important horizon of work for academia and professional practices in Physical Education and Sport, and, in turn, a possibility for scientific advancement.